The Effect of Hot Sun on the Compressive Strength of Concrete on the Sukoharjo – Hargosari Road Section - Putri Regina Wigatiningrum; Tantin Pristyawati; Marwahyudi; Dian Muhammad Rifai; Muhammad Yusuf Arifin (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
This study discusses how much influence the hot sun has on the strength of concrete. Concrete is widely used in construction, because it is cheap and easy to implement. Still, it also requires extensive knowledge regarding the nature of the basic concrete material, how to make it, and when to lay it so that it can produce maximum quality and quality when the concrete is laidThe  research aims to find out how much influence the hot sun during casting has on the compressive strength of concrete. In this research, test specimens were made for the concrete mixture with a design compressive strength of f'c = 20 MPa, using a cylinder with a diameter of 15 cm and a height of 30 cm, and strength testing. press approach using hammer test. Casting was carried out in the morning, afternoon, and evening with different types of sunlight on one road section. The results of this research show that the hot sun during casting affects the compressive strength of the concrete produced. The heat of the sun is too hot, causing the concrete that is laid to crack easily and its compressive strength is low even though the concrete has been covered with geoteck and watered regularly.